The Socialization of The Sound System and The Study of Acoustic in The House of Workship (Mosque) - et. al., Ajeng Mayang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mosque is the house of worship for moslem which are is used for many positive activities besides for routine worship, “shalat” five times a day. Those activities are discoursing, mentoring, reciting Al-Qur’an, marriage contract (“akad nikah”) activity, big day islam commemoration and others. To support those activities, the mosque need be supported by a great facilities and infrastructure. One of them is a good sound system. The great sound system has to meet the standards which had been applied by the instruction of General Director of Islamic Community Guidance No. Kep/D/101/1978 about Using The Sound System in Mosque, “Langgar”, Prayer Room (Mushola). In the other hand, we need to give attention to the electrical construction for sound system installation that will be used to get the great sound quality on the whole.